Absolute assignment in takāful industry: Sharī‘ah contracts, issues and solutions - Ibrahim, Ahmad Basri; Mohd Ali, Ahmad Fadhil Hamdi (IIUM Press, 2015)
This article deliberates on the Islamic contracts used in absolute assignment in takāful industry and identifies Sharī‘ah issues that might accrue from it. The article studies the market practice of absolute assignment in takāful industry in Malaysia and proposes the adequate Islamic contracts that can be used in absolute assignment and at the same time resolve any Sharī‘ah issues that might occur from it. This research consists of both library-based research and fieldwork research. The researchers interviewed some practitioners and studied the related documents and acts used in executing absolute assignment in takāful industry in Malaysia. The study infers that there are two types of absolute assignments. The first one is between an individual to an individual on the basis of hibah and the second one is between an individual and a financier/bank on the basis of kafālah.